Turning Points in Natural Theology from Bacon to Darwin - Peterfreund, S. author. aut Link
XVII, 193 p.
Keywords: Discusses crucial moments in the historical development of natural theology in England from the time of Francis Bacon to that of Charles Darwin. While the argument from design remains the rhetorical method of choice for natural theologians throughout the three centuries in question, the locus and object of design undergo a change.